2023
DOI: 10.1021/acs.macromol.2c02260
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Atom Upgrade to Polydicyclopentadiene

Abstract: Chemical cross-links within polymers increase mechanical strength and rigidity. Such cross-links can be either irreversible (e.g., those derived from carbon–carbon bonds) or reversible (e.g., those that depend on X–H···O hydrogen bonds). Here we describe a ketone-functionalized derivative of polydicyclopentadiene that establishes an unprecedented network of vinyl C–H···O hydrogen bonds within the polymer. The resulting thermoset displays a significantly increased glass transition temperature relative to the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In 2023, DiLabio, Wulff, and co-workers reported the allylic oxidation of dicyclopentadiene (1) under an air atmosphere (Scheme 2C). 16 However, these reaction conditions involved a very long time (27 days). Inspired by these reports, we aimed to develop reaction conditions suitable for the oxidation of dicyclopentadiene (1) and cyclopentadiene (7).…”
Section: Paper Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…In 2023, DiLabio, Wulff, and co-workers reported the allylic oxidation of dicyclopentadiene (1) under an air atmosphere (Scheme 2C). 16 However, these reaction conditions involved a very long time (27 days). Inspired by these reports, we aimed to develop reaction conditions suitable for the oxidation of dicyclopentadiene (1) and cyclopentadiene (7).…”
Section: Paper Synthesismentioning
confidence: 99%
“…First, we optimized the reaction conditions for the allylic oxidation of dicyclopentadiene ( 1 ) (Table 1 ). We screened a series of lamps for this reaction (entries 1–4) and found that under halogen lamp 16 irradiation, the desired enone 2 was obtained in 13% yield (entry 1). We examined the use of a fluorescence lamp 14 in this oxidation and the resulting enone 2 was obtained in 25% yield (entry 2).…”
Section: Table 1 Optimization Of Allylic Oxidation Of D...mentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] Nevertheless, its further application is restricted by the modest glass transition temperature (T g ≈ 130 °C), high coefficient of thermal expansion (CTE, up to 140 ppm °C−1 ), and relatively high k value. [14][15][16] Although the functionalization of DCPD monomers, [16,17] regulation of the catalyst loading, [18,19] and addition of norbornene-based cross-linkable co-monomers [14,20] have been shown to enhance the thermal and mechanical properties of PDCPD, the higher polarization of these monomers and comonomers, along with higher catalyst loading are usually unfavorable to improve the dielectric properties. In general, both decreasing the molecular polarization and introducing air pores (k air ≈ 1) are effective strategies for reducing material's k value.…”
Section: Introductionmentioning
confidence: 99%